Microstructure characteristics and mechanical behaviour of a selective laser melted Inconel 718 alloy - Liang Huang; Yan Cao; Gaohong Li; Yuanfei Wang (Journal of Materials Research and Technology, 2020)
In this study, an Inconel 718 alloy was prepared by selective laser melting (SLM) with a pre-alloyed powder, and the microstructure and mechanical behaviour of the fabricated parts were studied. First, the settled layer structure, composed of several interlaced ''perlage'' molten pools and molten channels, was captured by low-magnification optical microscopy (OM), and the formation mechanism was revealed by the Gaussian heat source distribution characteristics of the laser source used for the SLM fabrication. Second, high-magnification scanning electron microscopy (SEM) captured the different crystal structures in different fabricated positions; meanwhile, the ''cross-border growth phenomenon'' along the forming direction and the ''growth and distribution characteristics of the crystal'' in the radial direction (perpendicular to the forming direction) were also captured. By introducing the component super-cooling theory, the growth mechanism of crystal structures in different positions under a multi-dimensional temperature gradient heat conduction coupling mode is proposed. Finally, combined with transmission electron microscopy (TEM) and a mechanical properties test, it was found that the mechanical properties were between those of parts fabricated by casting and those by forging because the γ'' phase and γ' phase were distributed in the crystal, while the carbide phase and Laves phase were distributed in the intercrystal region. Keywords: Inconel 718 alloy, Gaussian heat source, Microstructure, Component super-cooling theory